Autoantibodies to IgE and FcεRI and the natural variability of spleen tyrosine kinase expression in basophils - MacGlashan, Donald (Journal of allergy and clinical immunology, 2019)
Secretion from human basophils and mast cells requires spleen tyrosine kinase (SYK) activity, but SYK expression is highly variable in the general population, and this variability predicts the magnitude of IgE-mediated secretion. One known mechanism of modulating SYK expression in human basophils is aggregation of FcεRI. This study examines the possibility that functional autoantibodies are present in a wide variety of subjects and, in particular, subjects whose basophils poorly express SYK. It also tests whether any found antibodies could modulate SYK expression in maturing basophils and whether interaction with FcγRIIb/CD32b modulates the effect. An experimental algorithm for classifying the nature of histamine release induced by serum from 3 classes of subjects was developed. The frequency of functional autoantibodies that produce characteristics concordant with FcεRI-mediated secretion was zero in 34 subjects without chronic spontaneous urticaria (CSU). In patients with CSU, the frequency was lower than expected, approximately 7%. For the 5 of 68 unique sera from patients with CSU tested that contained anti-FcεRI or anti-IgE antibodies, these antibodies were found to induce downregulation of SYK in both peripheral blood basophils and basophils developed from CD34+ progenitors. Blocking interaction of these antibodies with CD32b did not alter their ability to downregulate SYK expression. This study establishes that functional autoantibodies to IgE/FcεRI do not provide a good explanation for the variability in SYK expression in basophils in the general population. They do show that if antibodies with these characteristics are present, they are capable of modulating SYK expression in developing basophils.